An Empirically-based Statewide System for Identifying Quality Pre-Kindergarten Programs - Williams, Jeffrey M.; Landry, Susan H.; Anthony, Jason L.; Swank, Paul R.; Crawford, April D. (Education Policy Analysis Archives, 2012)
This study presents an empirically-based statewide system that links information about pre-kindergarten programs with children’s school readiness scores to certify pre-kindergarten classrooms as promoting school readiness. Over 8,000 children from 1,255 pre-kindergarten classrooms were followed longitudinally for one year. Pre-kindergarten quality indicators of intentional instruction, an early literacy focus, and professional development were key predictors of kindergarten outcomes. A latent profile analysis identified pre-kindergarten classrooms that were high on pre-kindergarten quality indicators and high on kindergarten outcomes (67.3%), low on pre-kindergarten quality and kindergarten outcomes (21.3%), or low on quality but high on outcomes (11.4%). The last group of classrooms was likely to serve middle-class children and not use the state program model. This project demonstrates how a scientific approach can inform stakeholders and parents about the effectiveness of early childhood programs.